Generative theme, thematic investigation and approach: a literature panorama (Research, Society and Development, 2020)
In this work, we present a bibliographic review on thematic research and generative themes by Paulo Freire. This review was based on the search for papers that spoke on generative theme, research or thematic approach in science education and that were present in the last 20 years in A1 and A2 magazines on the national scene. The analysis culminated in the classification and interpretation of the articles, relating them to Freire's theory. After performing the analyzes, we identified different forms of approaches and variations regarding the interpretation of Paulo Freire's theory. The objective of this work is to know a little more about Freire's theory and through the search, categorization and analysis of the articles, to understand how science teaching is being carried out through generative themes in the country. We can conclude that through the research it was possible to know the obstacles, difficulties and advantages found in dealing with Freire's theory and how it is possible to execute it.